Dynamics of Hand Hygiene Compliance Among Nurses: A Comprehensive Analysis Tthrough Systematic Literature Review - Fathur (PT FORMOSA CENDEKIA GLOBAL, 2024)
This articles examines the dynamics of nurse compliance with hand hygiene practices, a critical public health topic in preventing the spread of infectious diseases in healthcare settings. Systematic Literature Review (SLR) methodology was employed, drawing from peer-reviewed articles, conference papers, and relevant studies indexed in databases like Scopus, Web of Science, and Google Scholar. The review highlights significant variability in hand hygiene practices among nurses and identifies key influencing factors such as knowledge, availability of facilities, and the social environment within hospitals. The findings underscore the importance of a multifaceted approach, integrating educational initiatives from an early age and robust hospital policies to enhance compliance rates. Through a comprehensive theoretical review and empirical analysis, this research contributes to understanding the complexities behind simple practices like hand washing and proposes strategic interventions for improving nurse compliance in healthcare settings.